Konsep Waktu Dan Kehidupan Adat Masyarakat Jalawastu - Anita Amelia; Rizkia Apriliani; Aqilatul Lathifah; Wahyuana Endah Setianingrum (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the concept of time in the traditional life of the Jalawastu community in Brebes Regency, Central Java. The study used a descriptive qualitative method with an ethnographic approach. Data were obtained through observation using the Simak Libat Bicara (SLC) technique. The results show that the Jalawastu community still maintains the use of traditional time terms including isuk, beurang, burit, peuting, and sandikala in their daily lives. The concept of time not only functions as an activity marker but is also related to customs, rituals, beliefs, and agricultural activities. In addition, the community continues to maintain traditional values ​​amidst the development of modern technology.